Financing strategies for water and environmental infrastructure - Organisation for Economic Co-operation and Development (Paris : Organisation for Economic Co-operation and Development, 2003)
In many countries, an important obstacle to achieving environmental goals has been the failure to adequately address the associated financial issues: the costs of achieving environmental goals; how those costs could be minimized; and the challenge of matching costs with available resources. This volume presents a method to develop financing strategies for investment-heavy environmental infrastructure, such as urban water supply, wastewater collection and treatment, and municipal solid waste
The strategies, supported by the FEASIBLE computer model, were developed in several countries of Eastern Europe, Caucasus and Central Asia (EECCA), in EU accession countries, and China. They supported a process of dialogue and consensus-building among the key stakeholders involved in financing environmentally-related infrastructure, stressing realism, affordability, and the cost-effective use of resources in achieving infrastructure development and environmental goals. The application of FEASIBLE builds bridges between policy development and implementation.
Includes bibliographical references
Keywords: Water conservation -- Economic aspects; Environmental protection -- Economic aspects